2017
DOI: 10.1080/14767058.2017.1402879
|View full text |Cite
|
Sign up to set email alerts
|

Medical genetics and genomics training in obstetrics and gynecology residencies: are we ready for the future?

Abstract: Despite the growing importance of MGG in day-to-day OB/GYN practice, only a limited number of ACGME-accredited OB/GYN residency programs offer an MGG rotation. When compared to other noncore OB/GYN rotations, such as, ultrasound and family planning, any MGG rotation was significantly shorter. With clear evidence that MGG will continue to radically change practice of OB/GYN in the future, it is imperative that steps need to be taken to address this deficiency in training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As of December 2016, only 14.3% of Accreditation Council for Graduate Medical Education–accredited obstetrics/gynecology (OB/GYN) residency programs had dedicated medical genetics rotations within their residency curriculum. Of programs with dedicated training, the average training time was 0.52 months, a significantly shorter duration than spent on other noncore rotations such as family planning or ultrasound 18 . In 1 study, 42% of OB/GYN residents reported feeling that their genetics education in residency was insufficient 19 .…”
Section: Considerations and Challenges For Obstetrician-gynecologistsmentioning
confidence: 94%
See 1 more Smart Citation
“…As of December 2016, only 14.3% of Accreditation Council for Graduate Medical Education–accredited obstetrics/gynecology (OB/GYN) residency programs had dedicated medical genetics rotations within their residency curriculum. Of programs with dedicated training, the average training time was 0.52 months, a significantly shorter duration than spent on other noncore rotations such as family planning or ultrasound 18 . In 1 study, 42% of OB/GYN residents reported feeling that their genetics education in residency was insufficient 19 .…”
Section: Considerations and Challenges For Obstetrician-gynecologistsmentioning
confidence: 94%
“…Of programs with dedicated training, the average training time was 0.52 months, a significantly shorter duration than spent on other noncore rotations such as family planning or ultrasound. 18 In 1 study, 42% of OB/GYN residents reported feeling that their genetics education in residency was insufficient. 19 In addition, expanded carrier screening requires a different approach to counseling than the current standard practice model of offering carrier screening for only a select few disorders.…”
Section: Considerations and Challenges For Obstetrician-gynecologistsmentioning
confidence: 98%